Abjection, Masculinity, and Sacrifice: The Reek of Death in Game of Thrones. (August 2022) - Johnston, Susan
The masculinities of HBO's Game of Thrones (2011–2019) are marked not just by violence and exploitation, but by contingency, fragility, and abjection. This article draws on theories of abjection to read the abject masculinity of Sandor Clegane, Samwell Tarly, and Theon Greyjoy in the context of theories of hegemonic and hypermasculinity, and, through Greyjoy in particular, tracks his movement from hypermasculinity, through abjection and torture, to a custodial and sacrificial and thus life-giving masculinity, which stands in profound opposition to the hegemonic masculinity of power and domination.